Effects of cryotherapy and thermotherapy associated with static stretching on the flexibility of hamstring muscles - S.A. Silva; D.J. Oliveira; M.J.N. Jaques; R.C. Araújo (Desafio Singular, 2010)
The objective of the present study was to analyze the effect of cryotherapy and muscular warming on the flexibility of the hamstring muscles associated with three minutes of static stretching. Forty young male and female volunteers were randomly included in one of four groups: Group 1 - Control group, Group 2 - Three minutes of static stretching, Group 3 - Stretching preceded by warming using shortwave diathermy (20 minutes), and Group 4 - Stretching preceded by applying cryotherapy (20 minutes) to the posterior thigh region. The program consisted of three series of stretching during five consecutive days and flexibility was assessed by goniometric evaluations of the extensor angle of the knee at the beginning of the protocol, at the end of the day and at the end of the protocol. The intergroup comparison was made through ANOVA post-hoc Tukey and the intragroup by paired t test, all with 5% level of significance. The three experimental groups significantly increased their range of motion in relation to the control group. However, differences were not observed among groups submitted to the different stretching programs. In conclusion, increases in flexibility were due to stretching and did not depend on previous application of hyperthermia and/or hypothermia.